Practices of Third Wave Coffee: A Burundian Producer's Perspective. (7th February 2018) - Rosenberg, Lauren; Swilling, Mark; Vermeulen, Walter J V
Abstract: The relationship between coffee quality and sustainability is typically analysed using symbolic quality attributes, not material quality. This article provides a bottom‐up perspective of Burundi's current competitive advantage in the global coffee market: material quality. The research agenda was embedded within the operations of a Burundian coffee washing station and describes critical business practices for producing and selling high material quality coffee. We argue that these business practices represent quality governance mechanisms that are significantly different from the exogenous and fixed criteria of sustainability certifications and labels. Such quality governance mechanisms are an important trading trend to recognize and understand in a producing country such as Burundi that is unable to effectively compete in the certified coffee market because of the small size and irregularity of its supply. Copyright © 2018 John Wiley & Sons, Ltd and ERP Environment